The tyrosine 73 and serine 83 dephosphorylation of H1N1 swine influenza virus NS1 protein attenuates virus replication and induces high levels of beta interferon - Jinghua Cheng; Jie Tao; Benqiang Li; Ying Shi; Huili Liu (Virology Journal, 2019)
Abstract Background Nonstructural protein 1 (NS1) is a virulence factor encoded by influenza A virus (IAV) that is expressed in the nucleus and cytoplasm of host cells during the earliest stages of infection. NS1 is a multifunctional protein that plays an important role in virus replication, virulence and inhibition of the host antiviral immune response. However, to date, the phosphorylation sites of NS1 have not been identified, and the relationship between phosphorylation and protein function has not been thoroughly elucidated. Method In this study, potential phosphorylation sites in the swine influenza virus (SIV) NS1 protein were bioinformatically predicted and determined by Phos-tag SDS-PAGE analysis. To study the role of NS1 phosphorylation sites, we rescued NS1 mutants (Y73F and S83A) of A/swine/Shanghai/3/2014(H1N1) strain and compared their replication ability, cytokine production as well as the intracellular localization in cultured cells. Additionally, we used small interfering RNA (siRNA) assay to explore whether changes in the type I IFN response with dephosphorylation at positions 73 and 83 were mediated by the RIG-I pathway. Results We checked 18 predicted sites in 30 SIV NS1 genes to exclude strain-specific sites, covering H1N1, H1N2 and H3N2 subtypes and identified two phosphorylation sites Y73 and S83 in the H1N1 SIV protein by Phos-tag SDS-PAGE analysis. We found that dephosphorylation at positions 73 and 83 of the NS1 protein attenuated virus replication and reduced the ability of NS1 to antagonize IFN-β expression but had no effect on nuclear localization. Knockdown of RIG-I dramatically impaired the induction of IFN-β and ISG56 in NS1 Y73F or S83A mutant-infected cells, indicating that RIG-I plays a role in the IFN-β response upon rSIV NS1 Y73F and rSIV NS1 S83A infection. Conclusion We first identified two functional phosphorylation sites in the H1N1 SIV protein: Y73 and S83. We found that dephosphorylation at positions 73 and 83 of the NS1 protein affected the antiviral state in the host cells, partly through the RIG-I pathway.